2019
DOI: 10.1083/jcb.201803003
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic regulators TPX2 and Aurora A protect DNA forks during replication stress by counteracting 53BP1 function

Abstract: 53BP1 is a chromatin-associated protein that regulates the DNA damage response. In this study, we identify the TPX2/Aurora A heterodimer, nominally considered a mitotic kinase complex, as a novel binding partner of 53BP1. We find that TPX2/Aurora A plays a previously unrecognized role in DNA damage repair and replication fork stability by counteracting 53BP1 function. Loss of TPX2 or Aurora A compromises DNA end resection, BRCA1 and Rad51 recruitment, and homologous recombination. Furthermore, loss of TPX2 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 30 publications
6
52
0
Order By: Relevance
“…Moreover, (Byrum et al, 2019;Cantor, 2019) identified an interaction between TP53BP1 and TPX2, as well as its kinase partner Aurora A, during mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, (Byrum et al, 2019;Cantor, 2019) identified an interaction between TP53BP1 and TPX2, as well as its kinase partner Aurora A, during mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Complex (APC/C) ubiquitin ligase at mitotic exit 18,19 . However, AURKA is detectable in interphase cells and has been attributed a number of non-mitotic roles including ciliation control, cell cycle regulation of MYCNdependent transcription, DNA damage pathways and mitochondrial regulation [20][21][22][23] . Overall, there is a growing interest in the roles played by AURKA outside of mitosis and their contribution to its cancerpromoting activity.…”
Section: Aurka Undergoes Targeted Proteolysis In Every Cell Cycle Asmentioning
confidence: 99%
“…Recent studies of the effects of acute inhibition of AURKA during mitosis have concluded that it plays an important role during mitotic exit in regulating assembly of the anaphase spindle upon which sister chromatids are segregated [3][4][5]. AURKA also has a number of non-mitotic roles that include disassembly of the primary cilium, regulation of myc family transcription factors and response to replication stress [6][7][8][9][10]. We and others recently reported that AURKA constitutively regulates mitochondrial morphology and function [11,12] in addition to a previously reported role in promoting mitochondrial fission in mitosis [13].…”
Section: Introductionmentioning
confidence: 99%